2020
DOI: 10.1111/1471-0528.16275
|View full text |Cite
|
Sign up to set email alerts
|

Giving birth in Ethiopia: a spatial and multilevel analysis to determine availability and factors associated with healthcare facility births

Abstract: Objective To assess spatial variations in the use of healthcare facilities for birth and to identify associated factors. Design Cross-sectional analysis of population-and healthcare facility-based data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
(97 reference statements)
5
14
1
Order By: Relevance
“…Malawi, for example, has 82% of the country's administrative level-2 not meeting the target. Similarly, in Ethiopia, although the national average distance to EmONC facilities was 12.8 km, it varies from as long as 27.1 km in the Somali region to as short as a kilometre in bigger cities of Addis Ababa and Dire Dawa [ 32 , 38 ]. Similar phenomena were observed in Ghana, where 82% of women can access C-EmONC facilities within two hours in the metropolitan region of Greater Accra while only less than a quarter in the two predominantly rural Northern and Western regions [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Malawi, for example, has 82% of the country's administrative level-2 not meeting the target. Similarly, in Ethiopia, although the national average distance to EmONC facilities was 12.8 km, it varies from as long as 27.1 km in the Somali region to as short as a kilometre in bigger cities of Addis Ababa and Dire Dawa [ 32 , 38 ]. Similar phenomena were observed in Ghana, where 82% of women can access C-EmONC facilities within two hours in the metropolitan region of Greater Accra while only less than a quarter in the two predominantly rural Northern and Western regions [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the availability and accessibility of health facilities, the quality of the service at the facility strongly influenced maternal health care utilization. Studies in different countries of SSA confirmed that higher service quality at health facilities increases the odds of maternal health service utilization [ 38 , 46 , 51 ]. However, two studies in different parts of Ghana failed to find such an association [ 65 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ethiopia, only 48% of deliveries were assisted by skilled birth attendant [7]. Other studies conducted in different parts of Ethiopia also reported that institutional delivery ranges from 27 to 51% [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%